2019
DOI: 10.3390/en12081422
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Continuous Pretreatment of Corn Stover: A Comparison of Three Commercially Available Continuous Pulverizing Devices

Abstract: We determined the potential of three mechanical pulverizers—a continuous ball mill (CBM), an air classifier mill (ACM), and a high-speed mill (HSM)—in the continuous pretreatment of corn stover. The mean diameters of the pulverized biomasses were not significantly different in the three cases, and the glucose yields from the CBM-, ACM-, and HSM-pulverized samples were 29%, 49%, and 44%, respectively. The energy requirements and process capacities for the ACM and HSM were similar. We conclude that the ACM and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, it can be found that the conversion rate of organic waste is proportional to its particle size, but the energy consumed is also proportional to the particle size of lignocellulose, and it is obviously inappropriate to pursue a smaller size with a larger energy consumption. Although mechanical treatment does not produce inhibitory substances, its treatment is predicated on significant energy consumption - the main factor limiting its application in the industry - it is nonetheless a necessary step prior to the treatment of AOW [ 49 ].…”
Section: Pretreatment Of Lignocellulosementioning
confidence: 99%
“…Therefore, it can be found that the conversion rate of organic waste is proportional to its particle size, but the energy consumed is also proportional to the particle size of lignocellulose, and it is obviously inappropriate to pursue a smaller size with a larger energy consumption. Although mechanical treatment does not produce inhibitory substances, its treatment is predicated on significant energy consumption - the main factor limiting its application in the industry - it is nonetheless a necessary step prior to the treatment of AOW [ 49 ].…”
Section: Pretreatment Of Lignocellulosementioning
confidence: 99%
“…Easy to use, high reproducibility, economic feasibility, and high flexibility to operate in both wet and dry conditions for almost any polymer matrix make this technology amenable for largescale industrial applications (Piras et al, 2019). In terms of energy consumption, Gu et al (2019) pointed out that the size reduction of corn stover at the microscale consumed a low energy of 7.4 MWh/t. Despite the above advantages, the possibility of contamination, noise, and long operation time are some of the BM limitations (Piras et al, 2019).…”
Section: Process Conditions Main Findings Referencesmentioning
confidence: 99%
“…In terms of energy consumption, Gu et al. (2019) pointed out that the size reduction of corn stover at the microscale consumed a low energy of 7.4 MWh/t. Despite the above advantages, the possibility of contamination, noise, and long operation time are some of the BM limitations (Piras et al., 2019).…”
Section: Fiber Modification By Wet/dry Mechanical Treatmentsmentioning
confidence: 99%
“…Because of the insufficient knowledge regarding the principles of action of the modern mechanochemical equipment, the mechanochemical stages during the refining of biomass are often performed through trial and error. Again and again, the researchers’ own experience makes them draw an obvious conclusion—that the energy required for pretreating material until the same parameter (size, specific surface area, or reactivity) is achieved can differ several times depending on what equipment was chosen [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%